Children's Experiences and Awareness about Impact of Digital Media on Health. Issue 6 (3rd June 2018) - Cernikova, Martina; Smahel, David; Wright, Michelle F.
ABSTRACT: Previous research has focused on the associations between technology use and children's health, using mainly quantitative designs. This qualitative study describes technology's impact on physical and mental health from children's perspectives. The differences between children's experiences and awareness of the health-related consequences associated with digital media use were examined. Focus groups and interviews were conducted with children between the ages of 9 and 16 in nine European countries ( N = 368). Results of this study indicate that children's experiences of health-related technology impacts are different from their awareness of these impacts. Children's direct experiences with media were less extreme in contrast to their awareness of health problems, which typically involved extreme examples of possible consequences, such as killing people, kidnapping, blindness, and developing learning or psychological disorders. The results are discussed in the context of the "media panic" and "third person effect" theories.